Students' Perceptions of the Importance of Civic Education in Dealing with Social Media Disinformation Level - Firdha Amalia; Nia Lestari; Siti Nurkomala Dewi; Devita Alisiani (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study examines students' perceptions of the role of Civic Education (Civics Education) in dealing with disinformation on social media. Through qualitative and quantitative approaches, the research analyzes the gap between Civics Education learning and the challenges of contemporary digital literacy. Data were collected through questionnaires, focus group discussions (FGDs) and in-depth interviews. The results showed a correlation between the effectiveness of Civics learning and students' ability to identify disinformation, where students who engaged in critical analysis-based Civics learning showed a 27% higher score in identifying disinformation. The findings indicate the need to revitalize the Civics curriculum with an emphasis on digital literacy and digital citizenship as core components. The research recommends transforming the Civics learning model from a theoretical approach towards developing practical skills in evaluating digital information.